"Inoculations: The Social Politics of Time, Labor, and Public Good in COVID-America". (2021) - Klein, Jennifer
Abstract : "We are becoming a 24/7 workforce." —Fair Workweek Initiative "I Can't Breathe" —Eric Garner, George Floyd, Manuel Ellis, Derrick Scott, Byron Williams, Vincente Villela, Ngozi Mbegu, Willie Ray Banks, James Brown… On May 1, 2020, Justa Barrios, a New York City home-care worker and labor activist, passed away from COVID-19. After working twenty-four-hour shifts for fourteen years, Barrios had injuries and compounding medical issues, including asthma, stomach difficulties, and heart problems. Her doctor determined that she could no longer work twenty-four-hour shifts. Yet when the home-care agency received a letter from the doctor requesting Barrios be assigned to eight-hour shifts, the agency dropped her. Barrios fought back. She found her voice in the "Ain't I a Woman?!" Campaign; comrades described her as a "fearless leader." Stemming from an alliance among female immigrants and US-born garment, plastics, office, and home-care workers, via workers' centers such as the National Mobilization Against Sweatshops, this organizing effort has sought to end twenty-four-hour days—and the legally permissible practice of paying for only thirteen hours—in New York state through direct action, the courts, union arbitration, and state legislation prohibiting twenty-four -hour shifts. Women such as Justa Barros, Lai Yee Chan, Mei Kum Chu, Seferina Rosario, and Sileni Martinez see the "Aint I a Woman?!" Campaign as a "new women's movement fighting for control over our time, health, respect and payment." As a cross-racial group, members chose to invoke Sojourner Truth, who tied together the causes of slavery abolition and women's rights, emancipation from coerced labor and from patriarchy, the dignity of women's labor and the dignity of release from work. But this legislation, which would seem so obviously humane and jarringly anachronistic, has been stalled in the New York legislature and ignored by Governor Andrew Cuomo for over a year.